Módulos de formación eclesial, bíblico, teológico y pastoral para los jóvenes de la parroquia eclesiástica de Iñaquito - López Rodríguez, Carlos Alberto (2013)
The first chapter is about “The current youth reality”, especially about different aspects of the young people in the 21st century. It also investigates about the current trends of the Ecuadorian young people and their reality, such as the family, urban tribes, psychology, sociology, Ecuador’s politics, education, church. Furthermore, it analyzes “The sacraments in the ecclesial experience” and “The Latin American and the Caribbean Church’s exhortation to the young people”. The second chapter is about the “Iñaquito’s Parish current youth situation”, the field investigations and interviews that were conducted. The analysis concludes that the youth does not care about the Church because they prefer other activities. Moreover, the biggest problem of youth is the consumption of alcohol and the greatest challenges facing youth with their families are lack of understanding and communication. The third chapter includes the product with four educational modules about ecclesial,